Clinical management of vulvodynia tips and tricks - Graziottin, Alessandra (Springer, 2011)
Cronic vulvar pain, or "vulvodynia", is a common problem that can have a considerable impact on the wellbeing of patients. Despite being seen routinely in everyday clinical practice, it remains a neglected disorder that may take many years to diagnose. This book eases the way for physicians, including General Practitioners and Gynecologists, who are motivated to improve the lives of women suffering from vulvodynia. By offering a concise overview of the latest information on the diagnosis and management of vulvodynia, and its numerous comorbidities, in an easy to read, "tips and tricks" format, the book empowers physicians to rapidly and effectively address the complex and sensitive issues surrounding the disorder.